St. John’s Wort enhances the synaptic activity of the nucleus of the solitary tract - Vance, Katie M. (2014)
OBJECTIVE: St. John’s Wort extract, which is commonly used to treat depression, inhibits the reuptake of several neurotransmitters, including glutamate, serotonin, norepinephrine, and dopamine. Glutamatergic visceral vagal afferents synapse upon neurons of the solitary tract (NST); thus, we evaluated whether St. John’s Wort extract modulates glutamatergic neurotransmission within the NST. MATERIALS AND METHODS: We used live cell calcium imaging to evaluate whether St. John’s Wort and its isolated components hypericin and hyperforin increase the excitability of pre-labeled vagal afferent terminals synapsing upon the NST. We used voltage-clamp recordings of spontaneous miniature excitatory postsynaptic currents (mEPSCs) to evaluate whether St. John’s Wort alters glutamate release from vagal afferents onto NST neurons. RESULTS: Our imaging data show that St. John’s Wort (50 μg/mL) increased the intracellular calcium levels of stimulated vagal afferent terminals compared to the bath control. This increase in presynaptic vagal afferent calcium by the extract coincides with an increase in neurotransmitter release within the nucleus of the solitary tract, as the frequency of mEPSCs is significantly higher in the presence of the extract compared to the control. Finally, our imaging data show that hyperforin, a known component of St. John’s Wort extract, also significantly increases terminal calcium levels. CONCLUSION: These data suggest that St. John’s Wort extract can significantly increase the probability of glutamate release from vagal afferents onto the NST by increasing presynaptic calcium. The in vitro vagal afferent synapse with NST neurons is an ideal model system to examine the mechanism of action of botanical agents on glutamatergic neurotransmission.